102 Effect of engineered biocarbon on rumen fermentation, microbial protein synthesis and methane production in an artificial rumen (RUSITEC) fed a high forage diet. - McAllister, T (J Anim Sci, 2018)
The objective of this study was to investigate the effects of adding engineered biocarbon to a high forage diet on ruminal fermentation, nutrient digestion and enteric methane production in an artificial rumen system (RUSITEC). The experiment was a completely randomized block design with four treatments assigned to sixteen fermentation vessels (4/treatment) in two RUSITEC systems. The control diet consisted of 60% barley silage, 27% barley grain, 10% canola meal and 3% vitamin and mineral supplement (DM basis) with treatments consisting of biocarbon added at 0, 5, 10 and 20 g/kg of substrate DM. The study period consisted of 10-d adaptation and 7-d sample collection period. Data were analyzed by the PROC MIXED procedure of SAS with fixed effects of treatment, day of sampling and their interaction with the day of sampling as a repeated measure, and random effects of fermenter. Compared to control, addition of biocarbon linearly increased (P < 0.05) digestibility of DM (74.9 vs. 73.2%), OM (74.9 vs. 72.9%), ADF (36.8 vs. 29.9%), NDF (44.8 vs. 39.9%) and CP (86.2 vs. 84.3%). Increasing biocarbon enhanced (P < 0.01) production of total VFA, acetate, propionate and branch-chained VFA and tended to increase (P = 0.06) NH3-N. Compared to control,total microbial N production linearly increased (P = 0.01) with addition of biocarbon (96.1 vs. 85.7 mg/d). Addition of biocarbon reduced (P ≤ 0.05) methane production compared with the control (11.9 vs. 15.2 g/g DM digested). There were no differences (P > 0.05) in production of total gas, large or small peptides, or in the number of protozoa as a result of addition of biocarbon to the diet. The results indicate that addition of biocarbon up to 2% to a forage increased DM digestibility, while lowering enteric methane production and enhancing microbial protein synthesis in continuous flow fermenters.